Polyethylene glycol treated allografts not tissue matched nor immunosuppressed rapidly repair sciatic nerve gaps, maintain neuromuscular functions, and restore voluntary behaviors in female rats. Issue 7 (16th April 2018) - Mikesh, Michelle; Ghergherehchi, Cameron L.; Rahesh, Sina; Jagannath, Karthik; Ali, Amir; Sengelaub, Dale R.; Trevino, Richard C.; Jackson, David M.; Tucker, Haley O.; Bittner, George D.
Abstract: Many publications report that ablations of segments of peripheral nerves produce the following unfortunate results: (1 ) Immediate loss of sensory signaling and motor control; (2 ) rapid Wallerian degeneration of severed distal axons within days; (3 ) muscle atrophy within weeks; (4 ) poor behavioral (functional) recovery after many months, if ever, by slowly‐regenerating (∼1mm/d) axon outgrowths from surviving proximal nerve stumps; and(5) Nerve allografts to repair gap injuries are rejected, often even if tissue matched and immunosuppressed. In contrast, using a female rat sciatic nerve model system, we report that neurorrhaphy of allografts plus a well‐specified‐sequence of solutions (one containing polyethylene glycol: PEG) successfully addresses each of these problems by: (a ) Reestablishing axonal continuity/signaling within minutes by nonspecific ally PEG‐fusing (connecting) severed motor and sensory axons across each anastomosis; (b ) preventing Wallerian degeneration by maintaining many distal segments of inappropriately‐reconnected, PEG‐fused axons that continuously activate nerve‐muscle junctions; (c ) maintaining innervation of muscle fibers that undergo much less atrophy than otherwise‐denervated muscle fibers; (d ) inducing remarkable behavioral recovery to near‐unoperated levels within days to weeks, almost certainly by CNS and PNS plasticities well‐beyond what most neuroscientists currently imagine; and (e ) preventing rejection of PEG‐fused donor nerve allografts with no tissue matching or immunosuppression. Similar behavioral results are produced by PEG‐fused autografts. All results for Negative Control allografts agree with current neuroscience data 1‐5 given above. Hence, PEG‐fusion of allografts for repair of ablated peripheral nerve segments expand on previous observations in single‐cut injuries, provoke reconsideration of some current neuroscience dogma, and further extend the potential of PEG‐fusion in clinical practice. Abstract : PEG‐fused allografts rapidly and dramatically restore behaviors after segmental ablation of rat sciatic nerves.